2020
DOI: 10.1371/journal.pone.0238552
|View full text |Cite
|
Sign up to set email alerts
|

Obesity and smoking as risk factors for invasive mechanical ventilation in COVID-19: A retrospective, observational cohort study

Abstract: Purpose To describe the trajectory of respiratory failure in COVID-19 and explore factors associated with risk of invasive mechanical ventilation (IMV). Materials and methods A retrospective, observational cohort study of 112 inpatient adults diagnosed with COVID-19 between March 12 and April 16, 2020. Data were manually extracted from electronic medical records. Multivariable and Univariable regression were used to evaluate association between baseline characteristics, initial serum markers and the outcome … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 36 publications
(43 reference statements)
0
37
0
5
Order By: Relevance
“…Seven studies investigated the effect of age on the risk of intubation, using individuals hospitalized due to COVID-19. All studies were set in the USA (42, 55, 74, 82, 88, 91), and a summary of the results can be seen in Table S11. No studies had a low risk of bias (high quality), either due to the “confounding” or “exposure assessment” domain (Table S12).…”
Section: Resultsmentioning
confidence: 99%
“…Seven studies investigated the effect of age on the risk of intubation, using individuals hospitalized due to COVID-19. All studies were set in the USA (42, 55, 74, 82, 88, 91), and a summary of the results can be seen in Table S11. No studies had a low risk of bias (high quality), either due to the “confounding” or “exposure assessment” domain (Table S12).…”
Section: Resultsmentioning
confidence: 99%
“…Epidemiological studies continue to fuel conflicting results. While most of the studies to date have indicated an association between smoking and increased viral infection susceptibility and worsening of COVID-19 symptoms [24,[32][33][34][35][36][37][38][39][40][41][42][43][44][45], also highlighting the importance of the cumulative pack-year exposure [41], there are several studies that have observed an inverse relationship between smoking and COVID-19 [44,[46][47][48][49][50][51]. In particular, smoking prevalence among patients hospitalized with COVID-19 has been reported to be lower than the smoking prevalence in the general population [46,47,52] and these data were also confirmed in 132 patients who were admitted to our university hospital [53].…”
Section: Discussionmentioning
confidence: 99%
“…Data interpretation: Our three important findings are not independent of each other. Obesity is a recognized risk factor for COVID-19 infection and is associated with poor survival, particularly among patients treated in intensive care units and those requiring mechanical ventilation [13,14]. Obesity is known to be associated with a compromised immune system [15], in addition to the significant buildup of internal body fat, which has its mechanical effect in compromising normal physiological respiration including diaphragmatic and lung function [16,17].…”
Section: Discussionmentioning
confidence: 99%